2022
DOI: 10.1111/anae.15663
|View full text |Cite
|
Sign up to set email alerts
|

What can anaesthetists do to help combat the global climate emergency?

Abstract: The Intergovernmental Panel on Climate Change (IPCC) published its sixth assessment report in 2021 [1]. The report offers a stark and alarming warning that our climate is changing at an unprecedented rate due to human activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In terms of the language used to inform women about the environmental impact of different modes of labour analgesia, an emphasis on shared responsibility between clinicians and patients (‘our responsibility’) would help ensure a non‐judgemental stance. This shared responsibility emphasises that when delivering healthcare and upholding environmental sustainability principles, clinicians have a personal responsibility both to current patients and the broader population [29]. In another recent survey of postnatal patients at a UK hospital, 90% of respondents stated that they found information about the environmental aspects of labour analgesia alarming, and 76% reported that it would influence future choices [30].…”
Section: Pain Relief In Labourmentioning
confidence: 99%
“…In terms of the language used to inform women about the environmental impact of different modes of labour analgesia, an emphasis on shared responsibility between clinicians and patients (‘our responsibility’) would help ensure a non‐judgemental stance. This shared responsibility emphasises that when delivering healthcare and upholding environmental sustainability principles, clinicians have a personal responsibility both to current patients and the broader population [29]. In another recent survey of postnatal patients at a UK hospital, 90% of respondents stated that they found information about the environmental aspects of labour analgesia alarming, and 76% reported that it would influence future choices [30].…”
Section: Pain Relief In Labourmentioning
confidence: 99%